2016
DOI: 10.1021/acs.jpclett.6b00864
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Femtochemistry: Manipulating Nonadiabatic Dynamics at Avoided Crossings

Abstract: Molecular potential energy surfaces can be actively manipulated by light. This is usually done by strong classical laser light but was recently demonstrated for the quantum field in an optical cavity. The photonic vacuum state of a localized cavity mode can be strongly mixed with the molecular degrees of freedom to create hybrid field-matter states known as polaritons. We simulate the avoided crossing of sodium iodide in a cavity by incorporating the quantized cavity field into the nuclear wave packet dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
331
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(343 citation statements)
references
References 45 publications
9
331
1
Order By: Relevance
“…Polaritonic chemistry has become an emerging research field, aimed at providing new tools for the fundamental investigation of light-matter interaction. Since the pioneering experimental work carried out by the group of Ebbesen, in which they observed that strong light-matter coupling could modify chemical landscapes [8], the field of 'molecular polaritons' experienced much activity from both experimental [9][10][11][12][13][14][15][16][17][18][19] and theoretical [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] research groups. Recent achievements on molecules strongly coupled to a cavity mode, such as that strong cavity-matter coupling can alter chemical reactivity [9,38], provide long-range energy or charge transfer mechanisms [12,37], modify nonradiative relaxation pathways through collective effects [35], and modify the optical response of molecules [31,40], support the relevance of such a new chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polaritonic chemistry has become an emerging research field, aimed at providing new tools for the fundamental investigation of light-matter interaction. Since the pioneering experimental work carried out by the group of Ebbesen, in which they observed that strong light-matter coupling could modify chemical landscapes [8], the field of 'molecular polaritons' experienced much activity from both experimental [9][10][11][12][13][14][15][16][17][18][19] and theoretical [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] research groups. Recent achievements on molecules strongly coupled to a cavity mode, such as that strong cavity-matter coupling can alter chemical reactivity [9,38], provide long-range energy or charge transfer mechanisms [12,37], modify nonradiative relaxation pathways through collective effects [35], and modify the optical response of molecules [31,40], support the relevance of such a new chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In such theoretical descriptions, the molecules are usually treated with a reduced number of degrees of freedom or with some simplified models assuming two-level systems [20]. However, it is worth studying single-molecule cavity interactions as well, since a more detailed study of individual objects may also provide meaningful results [22,23,[40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Nonadiabatic molecular dynamics combined with machine‐learning strategies for the calculation of electronic‐structure quantities has recently emerged . Quantum electrodynamics effects have been introduced in nonadiabatic dynamics to investigate, for example, molecular dynamics in an optical cavity or the description of stimulated emission processes …”
Section: Discussionmentioning
confidence: 99%
“…The relationship between V and E is complicated and numerical models suggest that E is between 0 and 20 % smaller than V for activation energies E in the range being investigated here. [87,88] For 2-ethylanthracene (sample EA1), E DC = 16.0 AE 1.6 kJ mol À1 , e = 0.53 AE 0.11, y = 1.6 AE 0.3, and x = 0.30 AE 0.15. For 2-ethylanthraquinone (sample EAQ1), E DC = 17.5 AE 1.8 kJ mol À1 , e = 0.60 AE 0.12, y = 1.3 AE 0.3 and x = 0.50 AE 0.25.…”
Section: Modeling the Initial Relaxation Rates R Smentioning
confidence: 99%